Authentic Leadership and Proactive Behavior: The Role of Psychological Capital and Compassion at Work - Hu, Yixin; Wu, Xiao; Zong, Zhaobiao; Xiao, Yilin; Maguire, Phil; Qu, Fangzheng; Wei, Jing; Wang, Dawei (Frontiers in Psychology, 2018)
This study, which is based on survey data provided by 445 employees of a Chinese enterprise, examines the impact of authentic leadership on the proactive behavior of subordinates, in particular the mediating effect of subordinate psychological capital and the moderating effect of the compassion at work. The results of our structural equation model reveal that: (1) There is a significant positive correlation between authentic leadership and the proactive behavior of subordinates; (2) Psychological capital plays a full mediating role between authentic leadership and subordinate proactive behavior; (3) Compassion at work has a moderating effect on the positive relationship between authentic leadership and subordinate psychological capital and proactive behavior.